2020
DOI: 10.1177/1365480220958797
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the COVID-19 home-schooling experience: Listening to pupils, parents/carers and teachers

Abstract: In Spring 2020, schools in many countries had to close in response to the COVID-19 virus pandemic and move to remote teaching. This paper explores the views of pupils, parents/carers and teachers of ‘home-school’ in one Norwegian municipality, gathered through parallel online surveys in April 2020 during the peak of the COVID-19 lockdown period. It finds that adaptation happened very quickly and that home-school was well received by pupils and parents. There was more creative learning, better progress, more us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
224
3
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(269 citation statements)
references
References 9 publications
(9 reference statements)
19
224
3
23
Order By: Relevance
“…Nonetheless, interpreting findings in relation to existing literature suggests that the experiences of parents described by our analyses likely provide insights into typical mathematics experiences during COVID-19 emergency remote instruction. Moreover, studies from around the world (e.g., Norway, Indonesia, Nigeria), which focused on broader educational experiences, showed a similar increase in parental involvement in schooling during the initial transition to remote instruction [23,[37][38][39][40]. Looking across findings from recent studies on parents' experiences with emergency remote instruction during the early stages of COVID-19 suggests that our findings have broader implications despite the large number of participants from the United States.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Nonetheless, interpreting findings in relation to existing literature suggests that the experiences of parents described by our analyses likely provide insights into typical mathematics experiences during COVID-19 emergency remote instruction. Moreover, studies from around the world (e.g., Norway, Indonesia, Nigeria), which focused on broader educational experiences, showed a similar increase in parental involvement in schooling during the initial transition to remote instruction [23,[37][38][39][40]. Looking across findings from recent studies on parents' experiences with emergency remote instruction during the early stages of COVID-19 suggests that our findings have broader implications despite the large number of participants from the United States.…”
Section: Discussionsupporting
confidence: 54%
“…Such findings prompt initial optimism about the potential for sustaining high levels of parental engagement in school mathematics, which can promote higher levels of mathematics achievement [8], beyond the COVID-19 crisis [36]. Researchers in Norway also reported that emergency remote instruction provided greater opportunities for creative tasks within the school curriculum, especially for younger students; for teacher feedback through digital platforms; and for student independence to develop [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also important to consider that online teaching can lead to increased inequalities between children, further exposing those with a low socioeconomic background to adverse effects. A recent OECD-report [26] showed that schools have faced many challenges during COVID-19 school closures (e.g., poor availability of effective online platforms and poor technical skills among teachers). The report also emphasized that closing schools "has shed light on inequalities related to access to education, and on student well-being in the absence of social interactions and social services provided in schools" (p. 32).…”
Section: Resultsmentioning
confidence: 99%